Analysis of Community Resilience Level Based on Infrastructure Availability Perspective in Facing Mount Tangkuban Parahu Eruption - Adzila Fauziah; Juhadi Juhadi (Universitas Lambung Mangkurat, 2025)
The purpose of this study is to analyze the resilience level of the community based on the perspective of infrastructure availability in facing the potential eruption of Mount Tangkuban Parahu. The research is conducted in Lembang District, a tourist area surrounding Mount Tangkuban Parahu, which has a high vulnerability to volcanic eruption disasters. Volcanic eruptions can have significant impacts in the form of lava flows, lahars, volcanic gases, and steam that have the potential to damage the environment, cause material losses, and endanger human lives. In this context, the level of community resilience becomes a crucial aspect to minimize disaster risks. The type of research in this study is quantitative descriptive. The population in this research includes the community and infrastructure in the Lembang District area, with a sample of 50 respondents selected purposively. Primary data was collected through a questionnaire using a Likert scale (1-3), then analyzed descriptively with the help of SPSS version 25. Meanwhile, secondary data was obtained through documentation and official sources from relevant government agencies. The research results show that the level of resilience or endurance of the community in Lembang District based on infrastructure perspective is high with a resilience score of 2,37.